1992
DOI: 10.1136/bjo.76.7.419
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis following extracapsular cataract surgery: a review of 32 cases.

Abstract: Thirty two cases of endophthalmitis following extracapsular cataract surgery that had occurred within our department and had undergone intraocular diagnostic tap between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…Heaven et al 46 the 12 cases with negative culture. These results indicate that infectious PE could be more frequent in old people.…”
Section: Discussionmentioning
confidence: 99%
“…Heaven et al 46 the 12 cases with negative culture. These results indicate that infectious PE could be more frequent in old people.…”
Section: Discussionmentioning
confidence: 99%
“…S. epidermidis has been found to be the most frequent organism grown in endophthalmitis after cataract surgery [7, 11, 12, 13, 14]. Gallenga et al [15]in their in vitro study demonstrated a significant increase in S. epidermidis growth in different dilutions of viscoelastic substances containing sodium hyaluronate.…”
Section: Discussionmentioning
confidence: 99%
“…S. epidermidis has been found to be the most frequent organism grown in endophthalmitis after cataract surgery [3, 4, 5, 6, 7]. A scanning-electron-microscopy study by Jansen et al [12] showed massive colonization of the lens loop by S. epidermidis in a case of late-onset endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Staphylococcus epidermidis is the most frequent species isolated from the conjunctiva and lids in both healthy and infected patients [2], and it is the most common organism identified in endophthalmitis following cataract surgery [3, 4, 5, 6, 7, 8]. …”
Section: Introductionmentioning
confidence: 99%